PERANAN BADAN PENASEHAT PEMBINAAN, PELESTARIAN PERKAWINAN DALAM MENINGKATKAN KELUARGA SAKINAH (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study discusses the role of the Marriage Advisory and Preservation Advisory Board (BP4). The purpose of this study was to determine the Role of the Marriage Advisory and Preservation Advisory Board (BP4) in raising sakinah families in Tammero 'do Utara Village, Tammero' s Sendana Subdistrict, Majene Regency and the factors that could work BP4 in making sakinah families. Data sources in this study were obtained from direct interviews with several informants at the research location including the Chair and Deputy Chairperson of BP4, the Head of KUA, and Extension Workers. Data Processing and Analysis Techniques, namely the process through data reduction, data presentation, drawing conclusions, and verification. The results of this study indicate that the efforts made by KUA BP4 are: collecting family data in each hamlet, conducting a bride and groom course (suscatin), and pre-wedding courses, making working partner relationships, sakinah family coaching programs, and sermon safari programs. The obstacles are inadequate road access, lack of civil servant extension workers, and third parties in families interfering with the work of KUA BP4, as well as the lack of local government support.